Towards the use of multidimensional performance indicators in football small-sided games: the effects of pitch orientation - Folgado, Hugo (2019)
This study aimed to compare youth football players’ performance during two small-sided games with different pitch orientation: i) 40x30m and ii) 30x40m formats. Twenty under-15 players (age = 14.1 ± 0.5 years) participated in nine GK+4vs4+GK situations in each format, with the duration of six minutes each. Positional data were collected using individual GPS units, and computed for tactical and physical performance indicators. The SSG were video recorded, using notational analysis for collecting technical indicators. A novel method that incorporates time dependent notational information with spatiotemporal data was used to compute multidimensional parameters. Standardised effect sizes and non-clinical magnitude-based inferences were used to compare formats. Results showed that players covered more distance at higher intensities, presented more passes and dribbles and were more synchronised in the longitudinal axis while playing in the 40x30m pitch. In the 30x40m pitch, results showed a lower distance between team centroids, higher number of shots, more lateral passes and a wider team positioning. Multidimensional indicators, as players position and distance to the closest defender while shooting, revealed a more constant distance between attacker and defender in the 40x30m pitch. These results highlight the importance of integrating information from different indicators for a contextually valid information.